SAPONINAS EM TÃ‰PALAS NORMAIS E DEFORMADAS DE GLADÃOLO CULTIVAR ROSA DE LIMA - Mallozzi, P. R.; Barros, M. A. (REVISTA DE AGRICULTURA, 2015)
SAPONINAS EM TÃ‰PALAS NORMAIS E DEFORMADAS DE GLADÃOLO CULTIVAR ROSA DE LIMA